Czech and Polish understanding of democracy - Pająk-Patkowska, Beata; Pospíšilová, Jaroslava (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2019)
The paper attempts to analyze the results of the European Social Survey Round 6 (2012, 2013), focusing on the section related to how democracy is understood in Poland and in the Czech Republic. The most interesting issue encompassed the differences in how democracy is defined in the two countries and the outcomes these differences produce in terms of the perceived legitimacy of the system, as well as demographic factors that correlate with differences in the understanding of democracy in both surveyed groups. Statistical analyses carried out in the paper indicated the presence of different definitions of democracy formulated in Poland and in the Czech Republic (the Czechs gave stronger emphasis to the liberal aspect of democracy, whereas Poles stressed its social aspects more). Nevertheless, the relationship between the definition of democracy and the perceived level of legitimacy of the democratic system (for dispersed and specific legitimacy alike) were found to be relatively weak, as was the case of the relationship between the understanding of democracy, system legitimacy and socio-demographic factors. The only factor found to be significant for the perceived level of legitimacy of the democratic system concerned the level of satisfaction with one’s own material situation.